Group A streptococcal SpeB modifies IgA through targeting regions other than the hinge - Victoria Vassen; Emi Tanaka; Kirsten Moll; Christian Spoerry; Silvia Synowsky; Sally L. Shirran; Ulrich Schwarz-Linek; Edmund Loh; Mattias Svensson; Anna Norrby-Teglund (Microbiology Spectrum)
ABSTRACT Degradation of immunoglobulin (Ig) represents an important bacterial immune evasion strategy. For mucosal colonization, degradation of IgA is of particular importance, and many bacteria secrete specific IgA proteases that typically target the extended hinge region of IgA1. Such a specialized IgA protease has not yet been reported in Group A Streptococcus (GAS), despite its ability to successfully colonize human mucosal surfaces. In this study, we focused on the cysteine protease SpeB secreted by GAS and analyzed the interaction of SpeB with IgA. Assays using bacterial supernatants from wild-type and speB-deficient isogenic mutant strains, as well as recombinant SpeB, showed a SpeB-dependent IgA-modifying activity. SpeB resulted in the degradation of multimeric IgA, including the dimeric form, which was most notable in IgA2. The modification products were smaller in size than the heavy chain, suggesting a modification different from the classical hinge cleavage. Mass spectrometry analysis and glycosylation profiles indicated a putative cleavage in the C-terminal region, affecting the tailpiece and resulting in the loss of higher molecular weight multimeric/dimeric forms of IgA. Given the importance of dimeric IgA at mucosal surfaces, future studies are warranted to address whether IgA modification by SpeB represents a GAS immune evasion mechanism at this site.IMPORTANCEGroup A Streptococcus (GAS) is an important human pathogen with the ability to efficiently colonize mucosal surfaces and cause a wide spectrum of diseases ranging from pharyngotonsillitis to severe invasive infections or post-streptococcal sequelae. Immunoglobulins (Ig), in particular IgA, are critical effector molecules in the defense against pathogen colonization at mucosal surfaces. In this study, we focused on the cysteine protease SpeB, secreted by GAS, and investigated its interaction with human IgA. We report a SpeB-dependent IgA modification that involved the loss of multimeric/dimeric forms of IgA, predominantly affecting IgA2. The putative modification region is the C-terminus of IgA, which differs from the cleavage site of specialized IgA proteases targeting the hinge region. These findings suggest that IgA modification by SpeB might represent an immune evasion strategy utilized by GAS to colonize human mucosal tissue.